Cryptogein and capsicein promote defence responses in Quercus suber against Phytophthora cinnamomi infection - Medeira, Clara; Quartin, Virgínia; Maia, Isabel; Diniz, Inês; Matos, Mª Céu; Semedo, José Nobre; Scotti-Campos, Paula; Ramalho, José C; Pais, Isabel P; Ramos, Paula; Melo, Elvira; Leitão, António E; et al. (European Journal of Plant Pathology, 2012)
The decline of cork oak (Quercus suber) stands in Iberian Peninsula is associated with infection by Phytophthora cinnamomi. Most Phytophthora species secrete elicitins, which can enhance defence reactions against some pathogens. Here cytological and physiological effects of the elicitins cryptogein and capsicein on cork oak root infection by P. cinnamomi were evaluated. The progression of the pathogen in root tissue and its effects on total fatty acid (TFA) composition of roots and leaves were analysed in seedlings. Net photosynthesis (Pn), stomatal conductance (gs ), chlorophyll a fluorescence measurements (quantum yield of linear electron transport ϕe , photochemical quenching qP, non-photochemical quenching NPQ) and carotenoid determinations were carried out in well established (4 months) plants. In elicitin-treated roots, 2 days after inoculation, the pathogen which presented loss of viability and membrane degradation was mainly restricted to the intercellular spaces of the cortical parenchyma, and did not reach the vascular cylinder. Electron dense materials accumulated in the intercellular spaces of the cortex next to disorganized hyphae, suggested to be related with defence reactions. Cryptogein (or its interaction with P. cinnamomi) induced enhanced lipid synthesis in leaves, which may contribute to preserve membrane stability. P. cinnamomi decreased Pn , gs , ϕe , and qP, whereas elicitintreated plants displayed values similar to controls. Overall, the results indicated a resistance response of cork oak against this oomycete, induced by the elicitins.
Keywords: cytology; decline disease; fluorescence; leaf gas exchanges; Membrane Lipids; photosynthetic pigments

Impact of the Mediterranean Urban Environment on Photosynthetic Efficiency of Quercus ilex Leaves - De Nicola, Flavia; Alfani, Anna; D’Ambrosio, Nicola (Water, Air, & Soil Pollution, 2011)
Environmental constrains and anthropogenic changes can contribute simultaneously to the limitation of plant performance in Mediterranean urban areas. Photosynthetic efficiency of Quercus ilex L. leaves from the urban area of Naples was evaluated by comparison with leaves from remote site (Vesuvius National Park). The photosynthetic performance of leaves with different age (current year [CY], 1- [1Y] and 2-year old [2Y]) was assessed by measurements of gas exchange, chlorophyll fluorescence and pigment contents. The photosynthetic activity at the urban site was higher than that at the remote site for the CY leaves, while the opposite was observed for the 1Y and 2Y leaves. The growth of Q. ilex trees was mainly sustained by the CY leaves at the urban site, whereas at the remote site the photosynthetic activity was not affected by leaf ageing. In the urban environment, Q. ilex leaves strongly decreased the photosynthetic performance with leaf ageing as highlighted by leaf gas exchanges, although the photochemistry did not show any significant change. The mature leaves of urban site drove the reductive power deriving from the photochemistry more in nonassimilative processes rather than in carbon assimilative ones, avoiding a strong decrease of PSII photochemical efficiency
Keywords: chlorophyll fluorescence; environmental stress; leaf ageing; leaf gas exchange; photosynthetic pigments; urban; urban environmental stress

Seasonal changes in photosynthesis and photoprotection in a Quercus ilex subsp. ballota woodland located in its upper altitudinal extreme in the Iberian Peninsula - Corcuera, L; Morales, F; Abadía, A; Gil-Pelegrín, E (Tree Physiology, 2005)
Quercus ilex L. subsp. ballota (Desf.) Samp., a Mediterranean evergreen species growing in a continental Mediterranean climate, did not experience water stress and showed greater sensitivity to winter stress than to summer stress over a 12-month period. Net CO2 assimilation rates and photosystem II (PSII) efficiency decreased markedly during the cold months and recovered completely in spring. Lutein, neoxanthin and β-carotene to chlorophyll (Chl) molar ratios all showed the same trend throughout the year, increasing from September to March. This increase was a result of increases in carotenoid concentrations, because Chl concentration per unit leaf area remained stable, and was higher at the end than at the beginning of the first growing season. Lutein-epoxide was a minor component of the total lutein pool. Thermal energy dissipation and non-photochemical quenching (NPQ) were associated with the de-epoxidated forms of the xanthophyll cycle pigments in the warm months. Photosynthetic rates decreased slightly at midday in summer. These changes were accompanied by decreases in maximum potential PSII efficiency (which recovered during the night), actual and intrinsic PSII efficiencies, photochemical quenching and increases in NPQ. Overall, our data indicate down-regulation of photosynthesis during the summer. The diurnal de-epoxidation of violaxanthin to antheraxanthin and zeaxanthin occurred throughout the year, except in January. Antioxidant enzymatic activity increased in the winter months, especially during the coldest months, highlighting its key role in photoprotection against photo-oxidation. Structural and functional modifications protected PSII from permanent damage and allowed 1-year-old leaves to photosynthesize at high rates when temperatures increased in spring.
10.1093/treephys/25.5.599
Keywords: antioxidant enzymatic activity; chlorophyll fluorescence; photosynthetic pigments; summer stress; winter stress

Seasonal changes in photosynthesis and photoprotection in a Quercus ilex subsp. ballota woodland located in its upper altitudinal extreme in the Iberian Peninsula - Corcuera, L.; Morales, F.; Abadia, A.; GIL-PELEGRÍN, E. (Tree Physiology, 2005)
Quercus ilex L. subsp. ballota (Desf.) Samp., a Mediterranean evergreen species growing in a continental Mediterranean climate, did not experience water stress and showed greater sensitivity to winter stress than to summer stress over a 12-month period. Net CO2 assimilation rates and photosystem II (PSII) efficiency decreased markedly during the cold months and recovered completely in spring. Lutein, neoxanthin and β-carotene to chlorophyll (Chl) molar ratios all showed the same trend throughout the year, increasing from September to March. This increase was a result of increases in carotenoid concentrations, because Chl concentration per unit leaf area remained stable, and was higher at the end than at the beginning of the first growing season. Lutein-epoxide was a minor component of the total lutein pool. Thermal energy dissipation and non-photochemical quenching (NPQ) were associated with the de-epoxidated forms of the xanthophyll cycle pigments in the warm months. Photosynthetic rates decreased slightly at midday in summer. These changes were accompanied by decreases in maximum potential PSII efficiency (which recovered during the night), actual and intrinsic PSII efficiencies, photochemical quenching and increases in NPQ. Overall, our data indicate down-regulation of photosynthesis during the summer. The diurnal de-epoxidation of violaxanthin to antheraxanthin and zeaxanthin occurred throughout the year, except in January. Antioxidant enzymatic activity increased in the winter months, especially during the coldest months, highlighting its key role in photoprotection against photo-oxidation. Structural and functional modifications protected PSII from permanent damage and allowed 1-year-old leaves to photosynthesize at high rates when temperatures increased in spring.
10.1093/treephys/25.5.59910.1093/treephys/25.5.599
Keywords: antioxidant enzymatic activity; chlorophyll fluorescence; photosynthetic pigments; summer stress; winter stress

Influence of fire and tree-fell on physiological parameters in Quercus ilex resprouts - Fleck, I.; Grau, D.; Sanjose, M.; Vidal, D. (Ann. For. Sci., 1996)
Variations in the physiology of two kinds of resprout (originated after fire and after tree-fell) of Quercus ilex were analyzed under field conditions and compared with respect to the original, undisturbed vegetation, located within a Mediterranean watershed (northeast Spain). Resprouting vegetation of Quercus ilex after fire or after tree-fell showed, during the next growing seasons, enhanced photosynthesis, leaf conductance and Rubisco activity with respect to the original vegetation, especially under high temperature, irradiance and vapor pressure deficit (VPD). The lack of differences in nutrient (N,C,P,K and Ca) and soluble carbohydrate concentrations in leaves of resprouts originated after fire or after tree-fell indicates the independence of nutrients released by the action of fire and the contribution of underground organs. Differences in leaf mass per area (LMA) were due to increased thickness in resprouts whereas density was the same. N investment in chlorophylls or Rubisco was not different in control or either kind of resprout. The increased amount of carotenoids in resprouts contributed to providing protection from photoinhibitory processes
Keywords: fire; Gas exchange; Nutrients; photosynthetic pigments; Quercus ilex; tree-fell

Influence of fire and tree-fell on physiological parameters in Quercus ilex resprouts - Fleck, I; Grau, D; Sanjosé, M; Vidal, D (Ann. For. Sci., 1996)
Variations in the physiology of two kinds of resprout (originated after fire and after tree-fell) of Quercus ilex were analyzed under field conditions and compared with respect to the original, undisturbed vegetation, located within a Mediterranean watershed (northeast Spain). Resprouting vegetation of Quercus ilex after fire or after tree-fell showed, during the next growing seasons, enhanced photosynthesis, leaf conductance and Rubisco activity with respect to the original vegetation, especially under high temperature, irradiance and vapor pressure deficit (VPD). The lack of differences in nutrient (N,C,P,K and Ca) and soluble carbohydrate concentrations in leaves of resprouts originated after fire or after tree-fell indicates the independence of nutrients released by the action of fire and the contribution of underground organs. Differences in leaf mass per area (LMA) were due to increased thickness in resprouts whereas density was the same. N investment in chlorophylls or Rubisco was not different in control or either kind of resprout. The increased amount of carotenoids in resprouts contributed to providing protection from photoinhibitory processes
Keywords: fire; Gas exchange; Nutrients; photosynthetic pigments; Quercus ilex; tree-fell